Obtenção da curva de Intensidade-Duração-Frequência (IDF) de chuvas intensas para a bacia hidrográfica do Igarapé Murupu, Boa Vista-RR - Carvalho, Reinaldo Gama de (2007)
This research work has as main objective the definition of the curve Intensity–Duration–Frequency - IDF of intense rains of Boa Vista - RR, tends in view to be this city one of the rare without Brazilian capitals that fundamental tool to define the dimensions of works of the type: bridges, gutters, dams, canalization urban or rural, irrigation, erosion control, among others. The methodology known as disaggregation of the rain of "1 DAY" that left of given available pluviometer data of a 34 year-old historical series, observed from 1961 to 2007 for INMET in the station Boa Vista. The specific objectives was the estimates of the effective rainfall and of the design flood, of the river basin of the Murupu, with area of 790.6253 km², estimates with base in the model of Soil Conservation Service - SCS, consecrated internationally, that uses physiographic parameters of the basin where stands out the CN call Curve Number (Number of the Curve) that reflects the tax of infiltration of the s oil, in the hypothesis corresponding to the soils with humidity medium or equivalent the field capacity. The expression of curve Intensity–Duration–Frequency - IDF found for Boa Vista – RR was im = 951.57. T 0.161 / (t + 12) 0.76, whose results presented coherence with the origin data, made calculations with the model of Gumbel-Chow and for the curve IDF of the cities of São Paulo - SP, Cuiabá - MT, Goiânia - GO, Belém - PA, Manaus - AM, Rio de Janeiro - RJ and São Luiz - MA, for return periods from 5 to 100 years. The verification of the estimates of effective rainfall and of the design flood of the basin of the river basin Murupu demand measurements of field that was not possible. Therefore their results, even without discrepancies, they have its limited practical applications.